Priprava in uporaba prostorskih aktov - Hudoklin, Jelka (Podjetje in delo, 2016)
Spatial plans are general legal acts for spatial planning at the national and municipal levels. They are devised through procedures of spatial planning which is in the public interest and its main objective is to coordinate various interests. In most cases, the drafting of spatial plans is complicated and takes a lot of time, partly due to the provisions of spatial and sectoral legislation, and partly due to deficient knowledge and inappropriate actions of many stakeholders participating in the procedures. The problems in the application of spatial plans arise in terms of both general and detailed planning, on the one hand resulting from overregulation, and on the other hand due to disrespect or misinterpretation of provisions contained ordinances and decrees for various reasons.
Keywords: pravna ureditev; prostorski razvoj; prostorsko planiranje; Slovenija